Are We Getting Any Better? A Study on Repair Integrity in 1600 Consecutive Arthroscopic Rotator Cuff Repairs - McColl, Hayden (Orthop J Sports Med, 2016)
OBJECTIVES: Post-operative retear is the most common surgical complication following rotator cuff repair with reported rates ranging from 11% to 94%. There have been a number of advancements in the technology and management of rotator cuff repair which may have improved retear rates. The aim of this study was to determine if there has been any improvements in rotator cuff repair integrity in our centre and, to identify any changes in the management of rotator cuff tears that may have impacted post-operative re tear rate. METHODS: This observational single cohort study used running average analysis to examine 1600 consecutive patients who underwent primary arthroscopic rotator cuff repair by a single surgeon, and had cuff integrity assessed by ultrasound six months post operation. Exclusion criteria included revision rotator cuff repairs, isolated subscapularis repairs, and irreparable tears. RESULTS: Retear rates over the course of our study ranged from 3% to 34%, with the mean retear rate being 15%. The retear rate at the commencement of our study was 18% and decreased to 5% by the end. Reductions in retear were associated with; more passive rehabilitation, more attention to post-operative abduction sling use, increased surgical team experience. Increases in retear rates were associated with; increased false positives with a more sensitive ultrasound machine and, learning curves with new equipment for surgeon and sonographer. CONCLUSION: A significant decrease in retear rate following arthroscopic rotator cuff repair was observed over the course of our study with the re-tear rate at the end of the study being 5%. While the study design does not allow us to directly attribute changes in retear rate to changes in management, our results suggest that less aggressive rehabilitation, abduction sling use and increased surgeon experience decrease postoperative retear.